EMPOWERING THE EXACT SCIENCES: AN IMMERSIVE EXPERIENCE TO HIGHLIGHT THE LEADING ROLE OF WOMEN IN MATHEMATICS - Ferreira, José Gustavo Lima; Lopes, Kaike dos Santos; Brito, Silmara Mikaelly Souza; Pereira, Tiago Emanoel Melo (Seven Editora, 2025)
The article describes the successful experience of the 2024 Knowledge Fair at the Clóvis Nogueira Alves State Technical School (ETECNA), which addressed the theme of Women in Science, with a specific focus on the underrepresentation of women in the fields of Exact Sciences, in this case Robotics, Physics, Mathematics, and Statistics, seeking to rescue historical figures who are often invisible, such as Hypatia of Alexandria, Sophie Germain, Marília Chaves Peixoto, and Elza Gomide, in addition to connecting their trajectories to contemporary reality through a creative approach. To maintain the attention of the event’s target audience, which is mainly 9th-grade students, the exhibition was structured as a science fiction narrative, with time travel, theatrical performances, games, robots, and audiovisual resources, where the immersive experience brought science and pop culture to the same stage, making learning more playful and accessible. The preparation of educational products and the development of activities was carried out by groups of students separated into different thematic areas: History of Mathematics in Brazil, History of Mathematics in the World, Statistics/Probability, and Robotics. This resulted in a positive impact on two fronts: improving the interpersonal and academic skills of participating students, such as oral communication and teamwork, and successfully sparking visitors’ interest and awareness of the importance of diversity and women’s contributions in STEM fields. The conclusion reinforces the transformative potential of non-instrumental and innovative educational methods that use interactivity and creativity to promote scientific knowledge and social reflection, ensuring that even an area surrounded by prejudice such as mathematics can be palatable and interesting to all audiences, facilitating learning and enabling discussions on the subject. DOI: https://doi.org/10.56238/sevened2025.038-016